In-Situ Observations of Air Traffic Emission Signatures in the North Atlantic Flight Corridor - Schlager, H.; Konopka, P.; Schulte, P.; Schumann, U.; Ziereis, H.; Arnold, F.; Klemm, M.; Hagen, D.E.; Whitefield, P.D.; Ovarlez, J. (1997)
Focussed aircraft measurements have been carried out over the eastern North Atlantic to search for signals of air traffic emissions in the flight corridor region. Observations include NO, NO2, HNO3, SO2, O3, H2O, total condensation nuclei (CN), and meteorological parameters. A flight pattern with constant-altitude north-south legs across the major North Atlantic air traffic tracks was flown. Signatures of air traffic emissions were clearly detected for NOx , SO2, and CN with peak concentrations of 2 ppbv, 0.25 ppbv, and 500 cm-3, respectively, exceeding background values by factors of 30 (NOx), 5 (SO2), and 3 (CN). The observed NOx , SO2, and CN peaks were attributed to aircraft plumes based on radar observations of the source air traffic and wind measurements. Major aircraft exhaust signatures are due to relatively fresh emissions, i.e., superpositions of 2 to 5 plumes with ages of about 15 min to 3 hs. The observed plume peak concentrations of NOx compare fairly well with concentrations computed with a Gaussian plume model using horizontal and vertical diffusivities as obtained by recent large-eddy simulations, measured vertical wind shear, and the corridor air traffic information. For the major emission signatures a mean CN/NOx abundance ratio of 300 cm-3ppbv-1 was measured corresponding to an emission index (EI) of about 10|16 particles per 1 kg fuel burnt. This is higher than the expected soot particle EI of modern wide-bodied aircraft. For the most prominent plumes no increase of HNO3 concentrations exceeding variations of background values was observed. This indicates that only a small fraction of the emitted NOx is oxidized in the plumes within a timescale of about 3 hs for the conditions of the measurements.